2021
DOI: 10.1186/s40364-021-00314-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for immune-related adverse events: what have we learned and what lies ahead?

Abstract: Immune checkpoint inhibitors (ICIs) have heralded the advent of a new era in oncology by holding the promise of prolonged survival in severe and otherwise treatment-refractory advanced cancers. However, the remarkable antitumor efficacy of these agents is overshadowed by their potential for inducing autoimmune toxic effects, collectively termed immune-related adverse events (irAEs). These autoimmune adverse effects are often difficult to predict, possibly permanent, and occasionally fatal. Hence, the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 187 publications
(277 reference statements)
0
35
0
2
Order By: Relevance
“…The work by Berner et al supports the first hypothesis, as they found nine antigens shared between both the tumor and skin tissue [ 99 ]. Furthermore, many iAREs are associated with B and T-cell responses [ 104 , 105 ]. However, some studies also point the finger at myeloid-driven inflammation as a source of iAREs.…”
Section: Do Polyamines Prevent Autoimmune-mediated Eradication Of Tum...mentioning
confidence: 99%
“…The work by Berner et al supports the first hypothesis, as they found nine antigens shared between both the tumor and skin tissue [ 99 ]. Furthermore, many iAREs are associated with B and T-cell responses [ 104 , 105 ]. However, some studies also point the finger at myeloid-driven inflammation as a source of iAREs.…”
Section: Do Polyamines Prevent Autoimmune-mediated Eradication Of Tum...mentioning
confidence: 99%
“…Autoantibodies have been recognized as risk factors for irAEs, for example, TPO-Ab in thyroid dysfunction and islet antibodies in ICI-induced DM [99] . This is possibly because ICIs could both facilitate preexisting autoantibody-mediated immunity and trigger the production of autoantibodies by enhancing B-cell immunity [114] .…”
Section: Discussionmentioning
confidence: 99%
“…Considering immune-related adverse events related to anti-PD-1 mAbs administration and the success of PD-1 gene inactivation in primary human T cells, this strategy was extended to CAR-T cell therapy ( 326 ). Hu B. et al, designed CAR-T cells directed against CD133 and KO for the PD-1 gene by using the CRISPR/Cas9 technology, with an average of 91.5% of inactivated gene sites.…”
Section: Challenges and Engineering Strategies To Overcome Car-t Cell...mentioning
confidence: 99%